Penerapan model pembelajaran si-5 layang-layang (simayang) untuk meningkatkan keterampilan pemecahan masalah keliling dan luas bangun datar pada peserta didik kelas iv sekolah dasar - Fenni Sularsih (Universitas Sebelas Maret, 2020)
The purpose of this research was to describe the improvements of basic shapes measurements problem solving skills on fourth grade pupils in SDN Sumber III Surakarta during the implementation of Simayang teaching model. This research was conducted in 2 cycles classroom action research. The data were collected through observation, interview, test and documentation. This study targeted ≥80% of present pupils in the class reach the minimum proficiency score (≥75) on an essay test. The target was achieved on the second cycle where 20 from 25 pupils scored 75 or above on the test. Thus, it appeared that applying Simayang teaching model could improve basic shapes measurements problem solving skills of fourth grade elementary school pupils in SDN Sumber III Surakarta during the academic year 2018/2019. The improvement for each problem solving’s indicators differ on every phase of Simayang syntax. On phase I (orientation), the skills that were improving are “write down the information mentioned on the question in words” and “write down the information asked on the question”. On phase II (exploration – imagination), the skills that were improving are “representing the problem with drawing” and “choose the right problem solving strategic and relate it with the mathematic data mentioned on the question”. On phase III (internalization) and phase IV (evaluation), the improvements happen at all the indicators of basic shapes measurements problem solving skills. Simayang teaching model is recommended to be applied in a class that needs to improve the pupils’ problem solving skills.